Long noncoding RNA LINC00520 accelerates progression of papillary thyroid carcinoma by serving as a competing endogenous RNA of microRNA-577 to increase Sphk2 expression. Issue 7 (2nd April 2020) - Sun, Yu; Shi, Tiefeng; Ma, Yanfei; Qin, Huadong; Li, Kang
ABSTRACT: The long noncoding RNA (lncRNA) LINC00520 is an important modulator of the oncogenicity of multiple human cancers. However, whether LINC00520 is involved in the malignancy of papillary thyroid carcinoma (PTC) has not been extensively studied until recently. Therefore, the present study aimed to detect LINC00520 expression and evaluate its clinical significance in PTC. Functional experiments were conducted to test the biological role(s) and underlying mechanisms of LINC00520 in PTC progression. Reverse transcription quantitative polymerase chain reaction was performed to detect LINC00520 expression in PTC. A series of functional experiments, including Cell Counting Kit-8 assay, flow cytometry, Transwell migration assay, and tumor xenograft assay, was employed to investigate the biological roles of LINC00520 in PTC cells. High LINC00520 expression was verified in PTC tissues and cell lines, and this high expression was associated with the unfavorable clinicopathological parameters and short overall survival of patients. Functionally, LINC00520 interference resulted in a significant decrease in PTC cell proliferation, migration, and in vitro invasion and an increase in cell apoptosis. Further, its downregulation impaired tumor growth in vivo . Mechanistically, LINC00520 functioned as a competing endogenous RNA by sponging microRNA-577 (miR-577) and thereby increasing sphingosine kinase 2 (Sphk2) expression. Rescue experiments revealed that inhibiting miR-577 or restoring Sphk2 could abrogate the effects of LINC00520 silencing on the malignant phenotypes of PTC. LINC00520 functioned as an oncogenic lncRNA in PTC, and it facilitated PTC progression by regulating the miR-577/Sphk2 axis, suggesting that the LINC00520/miR-577/Sphk2 axis is an effective target in anticancer management.